2010
DOI: 10.1002/jnr.22526
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel small molecule activators of nuclear factor‐κb with neuroprotective action via high‐throughput screening

Abstract: Neuronal noncytokine-dependent p50/p65 nuclear factor-κB (the primary NF-κB complex in the brain) activation has been shown to exert neuroprotective actions. Thus neuronal activation of NF-κB could represent a viable neuroprotective target. We have developed a cell-based assay able to detect NF-κB expression enhancement, and through its use we have identified small molecules able to up-regulate NF-κB expression and hence trigger its activation in neurons. We have successfully screened approximately 300,000 com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…This is in agreement with the well recognized of role of NFKB in the signal transduction of TNF-alpha in many other systems including brain [4,7,16,24,30,36,40]. In fact, there is a paucity of evidence in the literature for TNF-alpha-initiated signaling proceeding through any other pathway besides one involving NFKB.…”
Section: Discussionsupporting
confidence: 89%
“…This is in agreement with the well recognized of role of NFKB in the signal transduction of TNF-alpha in many other systems including brain [4,7,16,24,30,36,40]. In fact, there is a paucity of evidence in the literature for TNF-alpha-initiated signaling proceeding through any other pathway besides one involving NFKB.…”
Section: Discussionsupporting
confidence: 89%
“…Based on the extensive literature on neuronal NF-κB activation, we tested the most-studied candidates. Supported by published data (Tamatani et al, 1999, Albensi and Mattson, 2000, Marchetti et al, 2004, Manuvakhova et al, 2011, Shim et al, 2011), the strongest and most consistent activator of NF-κB in neurons was TNFα. We employed multiple assays to demonstrate the response dynamics, and we compared the magnitude of the neuronal response to that in mixed brain cells.…”
Section: Discussionsupporting
confidence: 52%
“…For example, examination of assays listed in PubChem indicated that FLuc inhibitors can comprise more than half the hits derived from FLuc-based assays (Auld et al, 2008b) and reports have noted higher enrichments, approaching 98% (Lyssiotis et al, 2009; Younis et al, 2010). Nonetheless, such chemotypes have been considered as lead series, in part based on suggestive secondary assay data, although the target underlying the activity has yet to be identified (Manuvakhova et al, 2011; Xiao et al, 2011). Potent FLuc inhibitors have also been characterized from natural product extracts (Cruz et al, 2011) and have confused the interpretation of virtual screening results (Pang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%